Pengaruh Motivasi Belajar Dan Komitmen Organisasional Terhadap Prestasi Mahasiswa Studi Kasus Pada Mahasiswa Universitas Raharja - Rizka Mukhlisiah; Muhammad Acla Alamsyah Nurdin Hamzah; Mahendra Setiawan (IJAcc, 2022)
Student achievement is one of the main factors that need to be considered on campus to achieve the university's goals. Students are an important value owned by the university where all activities on campus can be carried out with the presence of students. One way that students are encouraged to study earnestly so that they can achieve optimal achievement, companies need to pay attention to learning motivation and organizational commitment. The purpose of this study is to find out and explain the influence of learning motivation and organizational commitment to student achievement in university students. The type of research used is survey research through google online form that is explanatory research. The number of samples in this study was 9 students. From the results of statistical analysis that learning motivation has a significant effect on student achievement variables, as well as learning motivation variables and organizational commitment variables have a significant effect on student achievement variables.